The effect of lesser yam tuber flour (Dioscorea esculenta) and cooking methods on meat analogue chemical and textural properties - Widya Karina Wijono; Teti Estiasih (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2021)
The addition of carbohydrates on gluten meat analogue has the potency to improve texture, such as lesser yam flour. It can be processed by steaming and baking. This study aimed to determine, analyze, evaluate the effect of cooking methods (steaming and baking) and substitution of lesser yam tuber flour (0%, 5%, 10%, 15%) on the texture of meat analogue and chemical properties only for the best meat analogue. This study used Randomized Block Design, Nested Design of 3 replications with 2 factors, levels of lesser yam tuber flour nested in cooking methods. The texture of meat analogue was compared to beef texture. The results showed that the cooking method affected hardness and cohesiveness significantly. The substitution of lesser yam tuber flour significantly affected hardness, springiness, cohesiveness and chewability. The best steamed meat analogue was at 5% substitution level of lesser yam tuber flour, contain of 49.79% moisture content, 28.39% protein, 17.04% carbohydrates, 2.57% ash, 2.21% fat and red grayish color. The best baked meat analogue was at 0% substitution level of lesser yam tuber flour, contain of 48.64% moisture content, 29.87% protein, 16.89% carbohydrates, 2.60% ash, 2.00% fat and red grayish color. The steamed meat analogue was more similar to beef, than the baked meat analogue. This production of a meat analogue would be suitable as a simple household-scale meat substituent.